Measuring the Economic Value of an Innovation When Some Investors Are Inattentive - Chemmanur, Thomas J.; Li, Dongmei; Tseng, Kevin; Wang, Yvonne Yu (Journal of Financial and Quantitative Analysis, 2026)
Abstract We analyze the effects of limited investor attention on the stock market reaction to innovation announcements and develop a new measure of patents’ economic value. We hypothesize that, when some investors pay delayed attention to innovation announcements, there will be a post-announcement drift in addition to the announcement effect, with the former decreasing and the latter increasing in investor attention. Using media coverage and abnormal Google search volume as investor attention proxies, we find consistent evidence. Our new attention-weighted measure of patents’ economic value has greater predictive power for future firm performance than measures based on the announcement effect alone.